Entrepreneurial orientation and market orientation on the performance of food and beverage MSMEs in Palembang City - Maulana, Ahmad; Novalia, Nurkardina; Sari, Dwi Darma Puspita; Rosa, Aslamia; Yuliansyah, Yuliansyah (Goodwood Publishing, 2024)
Purpose: This study analyzes how entrepreneurial and market orientation affect MSME performance in Palembang, emphasizing the role of competitive advantage as a moderating variable. Research Methodology: This study uses a survey method with data collection techniques through interviews with micro, small, and medium enterprise (MSME) owners and direct observation of the research object. The research population consists of 151 MSME entrepreneurs who live in Palembang. Results: The results showed that entrepreneurial orientation had a negative effect on performance. Testing the effect of entrepreneurial orientation on the performance of the value obtained a coefficient value of -0.090 with a p-valSSue of 0.008 <0.005, indicating that there is a significant influence, but no relationship between entrepreneurial orientation and the performance of food and beverage providers, and vice versa. Testing the effect of market orientation on the performance of Palembang city umkm through competitive advantage as a moderating variable with a coefficient value of 5.55 and a p-value of 0.00 <0.05 means strengthening the relationship between performance through competitive advantage as a moderating variable. Testing the effect of entrepreneurial orientation on the performance of Palembang city umkm through competitive advantage as a moderating variable with a coefficient value of 2.37 and a p-value of 0.00 <0.05 means strengthening the relationship between performance through competitive advantage as a moderating variable.